Analisis Financial Distress Dengan Metode Springate(s-score) dan zmijewski pada perusahaan food Andbeverage yang Terdaftar Di Bursa Efek Indonesia Periode 2013-2015 - Andika, Harum Suci; , Dr.Syamsudin,M.M (2017)
This study aims to identify and analyze the potential financial distress in manufacturing companies listed in Indonesia Stock Exchange sector food and beverage with use the Springate (S-Score) and Zmijweski model, as well as knowing the prediction model of financial distress proper used to predict a company's financial condition food and beverage. The data used is secondary data. Mechanical sampling using purposive sampling of 19 food and beverage companies listing on the Indonesia Stock Exchange acquired 17 companies that match the criteria. Analysis of the data used is qualitative data collection techniques documentation method. From the analysis of financial distress used the S-Score Springate model on Food and Beverage Companies in 2013-2015, companies experiencing distress condition of 21.57%.. The second model used a Zmijweski model. From this model calculation, the entire enterprise including non distress category or in good condition. Comparison of the two models, known that the right model is used to analyze the company's financial distress food and beverage is Zmijweski models.